SISTEM PENUNJANG KEPUTUSAN PENENTUAN BUAH TERBAIK MENGGUNAKAN METODE TOPSIS BERBASIS WEB (Studi Kasus: Toko Juz FoodyMoody) - Nufel Pahlevi (CV. Multi Kreasi Media, 2023)
The decision Support System (Decision Support System) is designed to produce various alternatives offered to decision makers, because most of the decisionmaking process is a form of selection from various alternatives to be selected, through certain mechanisms, in the hope of producing a good decision. The method used for decision selection is the Technique For Order Preferences by Similarity to Ideal Solution (TOPSIS) which can help find the optimal solution or alternative for a problem that will be displayed on a website-based basis. This method can help decisionmakers in situations where there are many alternative decisions with several criteria, for selecting the best fruit at the FoodyMoody fruit juice shop.